LAW ENFORCEMENT AGAINST ONLINE GAMBLING CRIMES AT THE MEDAN POLICE - Anggia Sammi Halomoan Siregar; Taufik Siregar; Rafiqi (SOSIOEDUKASI, 2026)
This thesis research is entitled Law Enforcement Against Online Gambling Crimes. The problem formulation is: (1) What are the legal regulations regarding gambling in Indonesian law? (2) How is the law enforcement against online gambling crimes at the Medan Police Headquarters? (3) What are the inhibiting factors in law enforcement against online gambling crimes at the Medan Police Headquarters? The research method used is normative juridical legal research, with a descriptive analytical research type. The problem approach uses a normative juridical approach. The data used are primary and secondary data. The results of the study show that (1) Gambling laws in Indonesian law consist of Law No. 11 of 2008 concerning ITE, Article 303 of the Criminal Code, Law No. 7 of 1974 concerning the Regulation of Gambling, and Articles 426 and 427 of Law No. 1 of 2023 concerning the Criminal Code. (2) Law enforcement against online gambling crimes at the Medan Police Headquarters involves conducting crime scene investigations and confiscating evidence used in online gambling. (3) The inhibiting factors in law enforcement against online gambling crimes at the Medan Police Headquarters include internal obstacles from law enforcement institutions and external obstacles in the form of increasingly sophisticated online gambling, including The use of encryption technology and servers located outside national jurisdiction can complicate the identification and enforcement process.